2017
DOI: 10.3389/feart.2017.00069
|View full text |Cite
|
Sign up to set email alerts
|

Pond Dynamics and Supraglacial-Englacial Connectivity on Debris-Covered Lirung Glacier, Nepal

Abstract: The hydrological systems of heavily-downwasted debris-covered glaciers differ from those of clean-ice glaciers due to the hummocky surface and debris mantle of such glaciers, leading to a relatively limited understanding of drainage pathways. Supraglacial ponds represent sinks within the discontinuous supraglacial drainage system, and occasionally drain englacially. To assess pond dynamics, we made pond water level measurements on Lirung Glacier, Nepal, during May and October of 2013 and 2014. Simultaneously, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(115 citation statements)
references
References 49 publications
5
110
0
Order By: Relevance
“…Thirdly, thermal UAV imagery could be applied in understanding the surface and subsurface hydrology. Englacial hydrology likely plays a key role in the drainage and transport of melt water through the glacier to the outlet (Miles et al, 2017), but the drainage paths are complex and difficult to measure. With a combination of thermal imagery, optical imagery, and the high-resolution DEM, it may be possible to infer supraglacial (sub-debris) and englacial drainage patterns.…”
Section: Applications Of Thermal Uav Imagerymentioning
confidence: 99%
“…Thirdly, thermal UAV imagery could be applied in understanding the surface and subsurface hydrology. Englacial hydrology likely plays a key role in the drainage and transport of melt water through the glacier to the outlet (Miles et al, 2017), but the drainage paths are complex and difficult to measure. With a combination of thermal imagery, optical imagery, and the high-resolution DEM, it may be possible to infer supraglacial (sub-debris) and englacial drainage patterns.…”
Section: Applications Of Thermal Uav Imagerymentioning
confidence: 99%
“…Meltwater storage on debris-covered glaciers varies seasonally and inter-annually. Some ponds coalesce and persist, whereas others drain seasonally upon interception with englacial conduits (Benn et al, 2012;Miles et al, 2017;Watson et al, 2017). Inhibited meltwater drainage leads to supra-and en-glacial water accumulation, and an increased likelihood of sporadic drainage.…”
Section: Changri Shar and Lhotse Glacier Outburst Floodsmentioning
confidence: 99%
“…The sub-aqueous calving occurred in supraglacial lakes could also lead to collapse of roof of englacial conduit which would accelerate the ablation process (Sakai et al, 2000;Benn et al, 2012). The backwasting of exposed ice-cliffs bordering the SGL also contribute significantly in the ablation process (Thompson et al, 2016;Miles et al, 2017). Thompson et al (2016) found that despite of small total area (5% of total ablation area), backwasting of ice-cliffs contributed to 40% in total mass loss in Nojumpa glacier.…”
Section: Temporal Evolution Of Lakesmentioning
confidence: 99%
“…Owing to the sizable impacts of glacial lake development, expansion and outburst, this field of cryospheric sciences has seen tremendous upsurge in research, which in turn has led to much better understanding of the controlling factors and mechanisms involved in evolution of the glacial lakes (Reynolds, 2000;Benn et al, 2012;Westoby et al, 2014;Thompson et al, 2016;Miles et al, 2017). Moraine-dammed lakes typically develop in overdeepened glacier bed behind the lateral and terminal moraine that were formed during the Little Ice Age (Benn et al, 2012;Westoby et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation